Modernização da mineração em Goiás e os efeitos territoriais da Orinoco Gold Limited no municípo de Faina/GO - Oliveira, Edgar da Silva (2020)
In the last decades of the twentieth century, the world's strongest population growth has increased the demand for natural resources in general and mineral resources specifically. In this context, Brazil has placed itself as one of the largest exporters of minerals in the world. In the same period the State of Goiás developed a whole techno-structure to reuse the mining areas from the 18th and 19th centuries and expand the range of exploited minerals in its territory. In this research we started from the hypothesis that the constitution of METAGO represented a paradigm shift for mining in Goiás that we call modernization. Considering that it is not only a change in the technique, but the implementation of a new productive logic from the changes in the position of the State. We also sought to perform a critical analysis of the territorial effects of Orinoco Gold Limited in the Municipality of Faina-GO. The first chapter entitled: Mining in Goiás-Tocantins and the constitution of Metais de Goiás S.A., aims to characterize and analyze the auriferous exploration that occurred in the eighteenth and nineteenth centuries in the territory of Goiano-tocantinense. The chapter also brings how Metais de Goiás S.A. contributed to the resumption of mining in the Goiano-tocantinense territory and, therefore, in the Fainense territory in the 20th century. The second chapter entitled: Geography, Nature and Mining: theoretical and methodological aspects, seeks to demonstrate, from a geographical reading, how social changes affect the relationship between society and nature, on the global and local scales, as well as to trace the evolution of the Brazilian legal-administrative body, focused on the mining sector, and its territorial effects (socioenvironmental). The third chapter: The Municipality of Faina-GO and the territorialisation of the mining company Orioco Gold Limited, brings the history of the territorial formation of the municipality. It also presents an analysis of the data obtained from the Brazilian Institute of Geography and Statistics regarding Faina/GO, its most recent experiences with mineral exploration, as well as the results of data obtained in the field.